ANALYSIS OF INDICATORS AND COST OF WORLD CLASS MAINTENANCE (WCM) IN FOREST MACHINES - Cavassin Diniz, Carlos Cezar; da Silva Lopes, Eduardo; de Magalhães Miranda, Gabriel; Soares Koehler, Henrique; Kremer Custodio de Souza, Eduardo (Floresta, 2019)
The study was carried out at a forest company located in the Paraná State, Brazil, with the feller buncher, skidder and harvester. The following indicators were evaluated: mechanical availability, mean time between failures, mean time to repair, proactive maintenance index and maintenance costs, based on data obtained over a period of 18 months, contemplating the stages of implantation, maturation and stabilization of the WCM. The results showed an increase in the mechanical availability of the cutting and skidding machines from the implantation stage. The mean time between failures increased from the implantation stage, from 31.59 hours to 37.01 hours in the stabilization stage. As for the mean time to repairs, skidder and harvester presented an increase of 25.9% and 18.9% respectively; however, this increase in time represented an improvement in the quality of maintenance services, reflected in the results of mean time between failures. There was also a 31% increase in the proactive index of the machines studied, resulting in 9% reduction in maintenance costs between the deployment and stabilization stages.